SGLT2 Inhibitors in Diabetic Patients With Cardiovascular Disease or at High Cardiovascular Risk: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhao, Zinan; Jin, Pengfei; Zhang, Yatong; Hu, Xin; Tian, Chao; Liu, Deping (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE: To investigate the effect of sodium-glucose cotransporter-2 inhibitors (SGLT2i) in diabetic patients with cardiovascular disease (CVD) or at high cardiovascular risk. DESIGN: Systematic review and meta-analysis of randomized controlled trials (RCTs). DATA SOURCES: Pubmed, Embase, the Cochrane Library, and ClinicalTrial.gov from their inception to 28 August 2021. REVIEW METHODS: RCTs assessing the effects of SGLT2i in diabetic patients with cardiovascular disease or at high cardiovascular risk. Primary outcomes included the composite outcome of cardiovascular death (CV death) and hospitalization for heart failure (HHF), HHF, and renal composite outcomes. Secondary outcomes included major adverse cardiovascular events (MACE), CV death, all-cause mortality, and change from baseline in HbA1c. Additionally, we assessed the effects of treatment in prespecified subgroups on the combined risk of primary and secondary outcomes. These subgroups were based on history of heart failure (HF), estimated glomerular filtration rate (eGFR) levels, and history of hypertension (HTN). A meta-analysis was carried out by using fixed effect models to calculate Hazard Ratio (HR) or Mean Difference (MD) between the SGLT2i and control groups. RESULTS: Four major studies (n = 42,568) were included. Primary outcomes showed that SGLT2i were associated with significantly lower risk of CV death/HHF (HR, 0.90; 95% Confidence Interval, 0.84 to 0.98; P for heterogeneity = 0.01), HHF (HR,0.84; 95% CI, 0.73 to 0.98; P = 0.02), and renal composite outcomes (HR, 0.83; 95%CI, 0.74 to 0.92; P = 0.0007) in diabetic patients with CVD or at high CV risk. Secondary outcome showed that the use of SGLT2i were associated with significantly reduction of the HbA1c level (MD, -0.30; 95%CI, -0.36 to -0.23; P < 0.00001). In subgroup analyses, SGLT2i significantly reduced the risk of renal composite outcomes in patients without history of HF (HR,0.75; 95%CI, 0.62 to 0.91; P = 0.003 < 0.025). No statistically significant were observed in other secondary outcomes and other subgroup analyses. CONCLUSIONS: SGLT2i showed moderate benefits on CV death/HHF, HHF, and renal composite outcomes in diabetic patients with CVD or CV risk. The benefits on improving renal composite outcomes were observed only in diabetic patients without HF history. SYSTEMATIC REVIEW REGISTERATION: PROSPERO CRD42021227400